Upaya Kepala Sekolah Dalam Meningkatkan Kualitas Guru di TK Negeri Pembina Sabak Auh Kec. Sabak Auh Kab. Siak Provinsi Riau - Zulfitri (UNISAN JURNAL, 2024)
This research aims to investigate the efforts made by school principals to improve the quality of teachers at the Pembina Sabak Auh State Kindergarten, Sabak Auh District, Siak Regency, Riau Province. Through a descriptive qualitative approach, data was collected through in-depth interviews with school principals, teachers and kindergarten administrative staff, as well as participatory observation in the school environment. Data analysis was carried out thematically to identify the main challenges, strategies used, and the impact of the principal's efforts on the learning process and children's learning achievements. The research results show that school principals are faced with various challenges in efforts to improve teacher quality, including the availability of quality human resources and changes in educational policies. However, through strategies such as training and professional development, coaching and motivation, as well as developing mentors and collaborative-based supervision, school principals have succeeded in overcoming these challenges. Apart from that, the school principal's efforts are also focused on the learning process and children's learning achievements, through designing relevant curricula, creating a supportive learning environment, and conducting regular evaluations and measurements of learning achievements. Keywords: Principal and Teacher Quality